2012
DOI: 10.3390/ijms131217295
|View full text |Cite
|
Sign up to set email alerts
|

Zhou, T.B., et al., Correction: All-Trans Retinoic Acid Treatment Is Associated with Prohibitin Expression in Renal Interstitial Fibrosis Rats. Int. J. Mol. Sci. 2012, 13, 2769-2782.

Abstract: The authors wish to change Figure 2 of the paper published in IJMS [1]. The positions of H1 and H2 in the previous article were reversed. These errors have been amended in an amended version of the manuscript, which is available from the International Journal of Molecular Sciences website. The authors and publisher apologize for the inconvenience. [...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…(UUO)-induced renal fibrosis model 8 , and retinoids have protective effects in numerous types of renal damage and inflammation including acute pyelonephritis 9 and glomerulosclerosis in adriamycin-induced nephropathy model 10,11 In addition, Chiba et al reported that atRA treatment reduced macrophage-dependent injury and fibrosis after an acute kidney injury (AKI), where atRA functioned to regulate macrophage activation 12 . These collective studies indicate that retinoids play a protective role in renal injury.…”
mentioning
confidence: 99%
“…(UUO)-induced renal fibrosis model 8 , and retinoids have protective effects in numerous types of renal damage and inflammation including acute pyelonephritis 9 and glomerulosclerosis in adriamycin-induced nephropathy model 10,11 In addition, Chiba et al reported that atRA treatment reduced macrophage-dependent injury and fibrosis after an acute kidney injury (AKI), where atRA functioned to regulate macrophage activation 12 . These collective studies indicate that retinoids play a protective role in renal injury.…”
mentioning
confidence: 99%